The Social Movement (Literacy Jihad) of Muhammadiyah Student Association to Face the Development of Science and Technology (IPTEK) in Balassuka Village, Tombolopao District, Gowa Regency - A, Ansurlawarlin (Indonesian Journal Of Economy Studies, 2024)
: This research discusses the Social Movement of the Muhammadiyah Student Association in addressing the development of science and technology (IPTEK) in Balassuka Village, Tombolopao District, Gowa Regency. The social movement in this context is the literacy jihad movement. Literacy Jihad is a movement carried out to promote the Iqro movement tradition, encouraging reading and writing among students or the younger generation. This literacy jihad is expected to be massively mobilized so that the next generation will not be blind to the changes of the times. The type of research conducted is qualitative research aimed at understanding the social movement (literacy jihad) of the Muhammadiyah Student Association in facing the development of science and technology (IPTEK) in Balassuka Village, Tombolopao District, Gowa Regency. Informants were determined through purposive sampling, based on the needs of informants such as the board of the Balassuka branch of the Muhammadiyah Student Association (IPM), the government, and the community in Balassuka. The data collection techniques used were observation, interviews, and documentation. The data analysis technique involved several stages: data collection, data exploration, data analysis, and conclusion drawing. Data validity was ensured using triangulation of technique, source, and time. The results of this study show that the social movement (Literacy Jihad) of the Muhammadiyah Student Association included activities such as nature contemplation, literacy classes, book discussions, and student dialogues.